(untitled) (Journal of the College of Basic Education, 2022)
The current research discussed the issue of cosmic communication, which was pardoned by most playwrights, due to the separation that occurred between the different sciences and the isolation of each discipline away from the other. The difference of their walks, especially the children among them, and the nature of the neurological and hormonal interactions that occur between the sender and the recipient, like the child, as well as between each of the actors among themselves, and the extent of the effect of focusing any of the vocabulary of the theatrical show on the type of response of the child receiver and its benefit to the child. The justifications for the research were determined by the following questions: Is there a type biological effects on